Asuhan Akupunktur Pada Penderita Generalized Anxiety di Klinik Akupunktur Kebun Rumput Cimahi - Wisnu, Rahmat; Wardoyo, Puspo; Candra , Leny (PT. Publikasiku Academic Solution, 2025)
Generalized Anxiety Disorder (GAD) is a mental condition characterized by excessive, irrational, and persistent anxiety that is difficult to control. This case study aims to evaluate the benefits of acupuncture treatment for a GAD patient at the Kebun Rumput Acupuncture Clinic in Cimahi. Employing a qualitative single-case design, the study involved six acupuncture sessions over a two-week period. Data were collected using the “Four Diagnostic Methods in Acupuncture” (inspection, listening and smelling, inquiry, and palpation), in accordance with Traditional Chinese Medicine (TCM) diagnostic principles. The results revealed significant improvements in both physical and psychological symptoms: anxiety subsided, sleep quality improved, somatic symptoms such as tongue dryness and pallor diminished, and vital signs indicated a more balanced Qi energy. Key acupuncture points used included HT7, PC6, Yintang, CV6, and KD3, aimed at calming the Shen, stabilizing the heart, and regulating Qi and Yin. This study concludes that acupuncture is an effective complementary therapy for GAD. The findings are expected to serve as a reference for clinical acupuncture practice and future research.